Performing a radical trachelectomy with uterine transposition in a patient with stage IB2 cervical cancer: A case report. (2023) - Chernyshova, Alena; Marchenko, Ekaterina; Chekalkin, Timofey; Kolomiets, Larisa; Chernov, Vladimir
Highlights: We describe a case of a woman with invasive IB2 cervical cancer requiring complex treatment. Suggested surgical approach with uterine transposition improves the existing RT procedure. Oncologic outcomes are encouraging, and no perioperative complications were noted. This case may represent a "milestone" in fertility-sparing surgeries. Abstract: We describe a case of a woman with invasive IB2 cervical cancer who desired to maintain fertility and required complex treatment. The suggested surgical approach with uterine transposition improves the existing radical trachelectomy procedure. Oncologic outcomes are encouraging, and no perioperative complications were noted. This report may represent a "milestone" in fertility-sparing surgeries, supporting the feasibility and safety of the opted method in stage IB2 cervical cancer with tumors about or smaller than 2 cm.